Study and Comparison of four Agent-Based Simulation Tools: Repast, SeSAm, Netlogo and GAMA (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Several simulation tools have been proposed in the literature and many surveys have been realized on this. The objective of this paper is not to give a survey but to compare four principal tools which are Repast, SeSAm, NetLogo and Gama according to some evaluation criteria that I consider important when designing Adaptive Multi-Agent Systems.